Pengaruh Air Gambut Terhadap Asphalt Concrete - Binder Courses (AC-BC) - Wardhana, Dheo; Malik, Alfian; Alwinda, Yosi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The road pavement mixture occasionally submerged in peat water and rain water. This research aims to determine the characteristics changes of AC-BC asphalt mixture through Marshall test. The mixture used asphalt pen 60/70. The specimens or mixture were soaked in two types of liquid namely peat water and rain water. The characteristics such as stability, flow, Marshall Quotient (MQ), void in mix (VIM), and void in mineral aggregate (VMA) and residual strength index (RSI) were measured using Marshall instruments. The immersion of asphalt using peat water and rain water have an impact towards its Marshall characteristics, respectively on the value of stability, flow, and VIM. The test showed that the stability value decreases with increasing of immersion age. At the age of 3 and 4 days after immersion in peat water and rain water, both asphalt stability values do not meet specifications according to general specification of Bina Marga 2018 with minimum value of 800 kg. Those result also showed that the specimens have damage faster than usual and reducing the strength of asphalt pavement. This loss of mixture strength leads to the decreased ability of the AC-BC mixture to bear the traffic load over the time then make it become plastic fatigue (flow). Then the research indicated that the value of the Residual Strength Index (RSI) gradually decreased since early ages. At the age of 2, 3, and 4 days of immersion of speciments showed in peat water, the value of RSI do not meet the specifications (more than 90%).Keywords: Peat water, Rain water, AC - BC